Acute endocarditis of a percutaneously placed pulmonary valve - Karthik V Ramakrishnan; Laura Olivieri; Richard A Jonas (Wolters Kluwer Medknow Publications, 2015)
Endocarditis of percutaneously placed pulmonary valve is increasingly being recognized and reported as a potentially life-threatening complication. In this report, we discuss a 17-year-old male who presented with septic shock secondary to staphylococcal endocarditis of a percutaneously placed pulmonary valve.